NEGATIVE IMPACTS OF PSYCHOLOGICAL PROBLEMS ON THE PROTAGONIST IN FAYE BIRD’S NOVEL MY SECOND LIFE - Dinda Femilya Utari; M. Manugeren (JOURNAL OF LANGUAGE, 2021)
The objective of this study is to find out the psychological problems on the protagonist and the negative impacts caused by the psychological problems in Faye Bird’s novel My Second Life published in 2014. Psychological problem are disorders of cognitive, volition, affective, and psychomotor generating to psychological disorders characterized by abnormal thoughts, feelings, and behaviors. The two aspects of the problems are in reality get into the corridor of psychology, a study about human’s soul or mind, either about its symptoms, processes, or its background. As literature is a reflection of society, all the characters are also members of literary community leading to a concept that psychology and literature are closely related.  This novel is about a teenager who experiences various psychological problems after finding out that in her first life she has been the cause of someone’s death. This study is conducted to give an overview to all people about the negative impacts of psychological problems experienced by the protagonist. This study applies qualitative method going through social phenomena and the data are collected from the novel. The results show the psychological problems are depression, anxiety and trauma causing negative impacts in the forms of insomnia, lack of concentration and truancy.